Stepwise LMA–fiberoptic bronchoscopy–double-lumen tube airway management for one-lung ventilation in a young patient with pulmonary hydatid cyst: a case report - Mesher Ensarioğlu; Ali Alagöz (Journal of Pulmonology and Intensive Care, 2026)
Airway management in thoracic surgery becomes challenging when the underlying pathology affects the airway, with additional complexity introduced when one-lung ventilation is required for surgical access. This report describes a 19-year-old male with no prior health issues, in whom a routine pre-employment chest radiograph identified a mass in the right upper zone. Further imaging with thoracic computed tomography revealed a 15×7 cm lesion in the right upper lobe's posterior segment, leading to compression of the trachea. The patient was referred for video-assisted thoracoscopic evaluation with an initial diagnosis of cystic lung disease. An airway management plan was prepared preoperatively, including a laryngeal mask airway (LMA), fiberoptic bronchoscope (FOB), bronchial blocker, and double-lumen tube (DLT). After standard monitoring, preoxygenation, and induction with midazolam, fentanyl, and propofol, an LMA was placed, and FOB examination showed near-complete extraluminal obstruction of the right main bronchus, with the left main bronchus remaining patent. The patient underwent video-assisted thoracoscopic surgery (VATS) for cyst resection, and postoperative analgesia was provided via ultrasound-guided erector spinae plane block (ESPB). Histopathological examination of the resected material confirmed the diagnosis of pulmonary hydatid cyst. This step-by-step approach, utilizing LMA, FOB, and DLT sequentially, can effectively maintain airway security in cases where mass-related airway compression complicates lung isolation during thoracic procedures.